Estimating General Equilibrium Spillovers of Large-Scale Shocks - Huber, Kilian (Review of Financial Studies, 2023)
Abstract Large-scale shocks directly affect some firms and households and indirectly affect others through general equilibrium spillovers. In this paper, I describe how researchers can directly estimate spillovers using quasi-experimental or experimental variation. I then argue that spillover estimates suffer from distinct sources of mechanical bias that standard empirical tools cannot resolve. These biases are particularly relevant in finance and macroeconomics, where multiple spillover channels and nonlinear effects are common. I offer guidance on how to detect and overcome mechanical biases. An application and several examples highlight that the suggested methods are broadly relevant and can inform policy and multiplier calculations. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.